Exploring open innovation approaches adopted by small and medium firms in emerging/growth industries: case studies from Daegu–Gyeongbuk region of South Korea. (18th January 2012) - Yun, Jin-Hyo Joseph; Mohan, Avvari V.
This study explores the status of open innovation in small and medium firms that operate in emerging or growth technological industries that have been designated as new growth engines in the Daegu–Gyeongbuk district in South Korea. Chesbrough (2003, 2006a, b) had demonstrated that the motive power of growth and development of big enterprises, be it in hi-tech or lowtech industries of USA, is 'open innovation'. Studies that followed examined the relationship between open innovation and industry performance had focused considerably on developed/mature industries. Though they analysed open innovation of small and medium firms, their analysis was limited to statistical relationships between open innovation and industry performances. Through the case studies this study's findings indicate that small and medium firms in South Korea seem to be dynamically adopting open innovation in the process of changing their business lines to more prospective hi-tech areas for their existence. It also seems that continuous growth and development could not be expected with closed innovation, and that the existence of small and medium firms can be threatened during verification period because it takes considerable time to get approval or support form markets or science and technology business circle.